Arabidopsis downy mildew effector HaRxL106 suppresses plant immunity by binding to RADICAL‐INDUCED CELL DEATH1. Issue 1 (29th August 2018) - Wirthmueller, Lennart; Asai, Shuta; Rallapalli, Ghanasyam; Sklenar, Jan; Fabro, Georgina; Kim, Dae Sung; Lintermann, Ruth; Jaspers, Pinja; Wrzaczek, Michael; Kangasjärvi, Jaakko; MacLean, Daniel; Menke, Frank L. H.; et al.
Summary: The oomycete pathogen Hyaloperonospora arabidopsidis ( Hpa ) causes downy mildew disease on Arabidopsis . To colonize its host, Hpa translocates effector proteins that suppress plant immunity into infected host cells. Here, we investigate the relevance of the interaction between one of these effectors, HaRxL106, and Arabidopsis RADICAL‐INDUCED CELL DEATH1 (RCD1). We use pathogen infection assays as well as molecular and biochemical analyses to test the hypothesis that HaRxL106 manipulates RCD1 to attenuate transcriptional activation of defense genes. We report that HaRxL106 suppresses transcriptional activation of salicylic acid (SA)‐induced defense genes and alters plant growth responses to light. HaRxL106‐mediated suppression of immunity is abolished in RCD1 loss‐of‐function mutants. We report that RCD1‐type proteins are phosphorylated, and we identified Mut9‐like kinases (MLKs), which function as phosphoregulatory nodes at the level of photoreceptors, as RCD1‐interacting proteins. An mlk1, 3, 4 triple mutant exhibits stronger SA‐induced defense marker gene expression compared with wild‐type plants, suggesting that MLKs also affect transcriptional regulation of SA signaling. Based on the combined evidence, we hypothesize that nuclear RCD1/MLK complexes act as signaling nodes that integrate information from environmental cues and pathogen sensors, and that the Arabidopsis downy mildew pathogen targets RCD1 to prevent activation of plant immunity.